Development of Student Worksheets Based on a Scientific Approach to Colloidal System Material - Nurlina, Nurlina; Ozsen, Zeynep; Jiyane, Lindiwe (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2024)
The purpose of this study was to determine the feasibility of developing student worksheets based on a scientific approach, student responses and teacher responses to the developed student worksheets. The type of research used was research and development with a 4D model. The instruments used in this study were validation sheets and response questionnaires. Before the field trial was conducted, the student worksheets were validated by a team of experts to determine the shortcomings of the student worksheets, then revised and tested. The results showed that the average percentage obtained from the media expert validator was 80.66%, material experts 85.33%, and language experts 82.66%, with an average percentage of 82.88%, this indicates that the student worksheets can be used with feasible criteria. The percentage obtained from the results of student responses was 34% very interested, 55% interested, and 11% less interested. The percentage of teacher response results was 25% very interested, 65% interested, and 10% less interested, this shows that the student worksheets developed can be used in State Islamic High School 5, Aceh Besar. Research on the development of student worksheets based on a scientific approach to colloidal system material offers innovation in more interactive learning, encourages conceptual understanding through exploration and experimentation, and improves students' critical thinking skills.